Irregular migration as an international problem: Risks and options - Steffen Angenendt (Stiftung Wissenschaft und Politik (SWP), 2008)
Irregular migration is one of the fastest-growing forms of migration worldwide. For many countries it presents a serious challenge. It undermines state sovereignty, calls into question the legitimacy of government action, and brings with it numerous risks for state, social, and individual security. To reduce the number of irregular immigrants, many countries have invested significant sums of money in recent years to develop instruments of governance and control. Up until now, however, these efforts have failed to produce the desired results.The study examines this phenomenon from a global perspective. It explains why irregular migration has become a global problem, defines the concepts that are central to this issue and provides an overview of current trends. The study also addresses political challenges - particularly the challenge of governance and the problems and risks associated with irregular migration - and it describes the various instruments of governance and control used at the national level, and the (still largely rudimentary) regional and international approaches to solving the problem.Finally, the study offers recommendations for European policy-makers. As a basic principle, every effort to reduce irregular migration should be founded on clarity and realism. Since isolated, short-term national measures are not appropriate for curbing irregular migration on an ongoing basis, comprehensive, long-term, internationally coordinated approaches must be chosen to link the different domestic, foreign, and development policy instruments. It is also in the interest of the receiving countries to eliminate deficits in the human rights protection of irregular migrants. To this a number of specific recommendations for European policy makers are added
Keywords: 320